The Cautionary Tale of Brian B. - Ward, James (Canadian Journal of Counselling and Psychotherapy, 2012)
The difficulties of providing adequate treatment experiences during training are discussed with reference to the inter-dependence of symptoms within family groups. To illustrate this the treatment of an eleven-year-old boy at a child guidance clinic is described. During this, several instances of gross psychopathology within the family group emerged which exposed the limitations of the initial treatment model. The case is discussed with respect to internalization of treatment models during training.